Legal Aspects of Electronic PPAT Deed in the Land Registration System in Indonesia - Nizam Zakka Arrizal; Bambang Eko Nugroho (CV. Akira Java Bulu, 2025)
The Indonesian government is implementing an electronic system in every aspect of government activities, and the land registration system in our country is no exception. The dynamics of the policy were turbulent in the community, Electronic land registration for community land was suspended because the regulation was rejected by some community members. The effort of government services in electronic form is the digitalization of government which refers to the transformation of manual systems and processes to digital systems in governance. This transformation aims to improve public services that are efficient, effective, transparent and accountable. Since the law regulating electronic land registration is still relatively new and has become a debated issue in the community, the author is interested in examining how the juridical aspects of electronic PPAT deeds in the land registration system in Indonesia relate to these issues. The research method used is normative juridical with a statutory approach. The results show that Ministerial Regulation No.3 of 2023 concerning the Issuance of Electronic Documents in Land Registration Activities is the latest reference in the land registration system in Indonesia which aims to convert land certificates into a digital system to oversee land activities, but there is no legal certainty in PPAT's policy to make authentic deeds electronically at this time because it does not have a legal basis.